The Development of Marijuana Dealing Behavior During Adolescence and Early Adulthood Among Juvenile Offenders: Risk Factors for Development. Issue 11 (1st November 2020) - Wojciechowski, Thomas
ABSTRACT: Despite the amount of attention paid to marijuana use, there has yet to be any research that examines heterogeneity in the development of marijuana dealing behavior across time. This research used group-based trajectory modeling to elucidate developmental trends in this behavior and examines how risk factors may predict heterogeneity in marijuana dealing among a sample of juvenile offenders. The Pathways to Desistance data set, a sample of 1, 354 juvenile offenders followed across 84 months during adolescence and early adulthood following a recent adjudication, was utilized in analyses. Results indicate that a five-group model best fits the data. Results indicate that higher baseline resistance to peer influence was associated with increased risk of assignment to the Accelerating and High Chronic groups, whereas baseline marijuana use was associated with assignment to the Accelerating, Desisting, and High Chronic groups when all covariates were included in estimation. This indicates that juvenile offenders may be at risk for dealing marijuana during adolescence and use of the drug and low susceptibility to peer influence may indicate higher risk for engagement.